Optimization of Hydrolysis Conditions, Isolation, and Identification of Biologically Active Peptides Derived from Acheta domesticus for Antioxidant and Collagenase Inhibition - Kankanit Yeerong; Panuwan Chantawannakul; Songyot Anuchapreeda; Sutee Wangtueai; Wantida Chaiyana (MDPI AG, 2024)
The study aimed to optimize hydrolysis conditions and isolate and identify bioactive peptides with anti-skin aging effects from Acheta domesticus (house cricket). A. domesticus proteins underwent hydrolysis using Alcalase® and optimized conditions using response surface methodology through a face-centered central composite design. Variable controls (enzyme-substrate concentration (E/S), time, and temperature) were assessed for their impact on activities against collagenase, 2,2-diphenyl-1-picrylhydrazyl radical (DPPH●), and degree of hydrolysis of protein hydrolysate (PH). PH was also investigated for composition, anti-skin aging, and anti-inflammatory effects. Amino acid sequences with potent anti-skin aging activity were isolated and identified using ultrafiltration, gel filtration chromatography, and liquid chromatography coupled with tandem mass spectrometry, employing de novo sequencing. Optimal conditions for producing PH with maximum anti-skin aging activity were an E/S concentration of 2.1% (w/w), 227 min, and 61.5 °C. Glutamic acid was a predominant amino acid and PH exhibited a molecular weight below 15 kDa. Additionally, PH displayed significant activities against collagenase, hyaluronidase, DPPH●, lipid peroxidation, and NF-κB-mediated inflammation (p < 0.05). Three novel anti-skin aging peptides were identified-Ala-Val-Thr-Lys-Ala-Asp-Pro-Tyr-Thr-Asp-Gln, Thr-Val-Met-Glu-Leu-Asn-Asp-Leu-Val-Lys-Ala-Phe, and Val-Pro-Leu-Leu-Glu-Pro-Trp-exhibiting the most potent collagenase and DPPH● inhibition. Therefore, this study proposed that PH, produced with Alcalase® under optimal conditions, emerges as a promising substance with potent anti-skin aging activity for the cosmeceutical industry.